2012
DOI: 10.4025/actascihealthsci.v34ispec.11938
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and functional status of elderly people of a long stay institution of the municipality Divinópolis, Minas Gerais State, Brazil

Abstract: This study aimed to evaluate and characterize the functional capacity and cognitive status of elderly people living in a long-stay institution of the municipality of Divinópolis, Minas Gerais State. The population consisted of 67 elderly people aged between 62 and 102 years, 76% female and 24% male. Data were gathered using the Barthel index of the Mini-Mental State Examination (MMSE) and a form for the social characterization. A significant correlation was observed between the Barthel index and the MMSE, i.e.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…A preservação das necessidades do idoso perfaz um caminho que ocasiona a valorização da sua autonomia e eleva a autoestima, apropriando-se de intervenções que previnam o declínio cognitivo e a preservação das habilidades mentais (MELLO; HADDAD; DELLAROZA, 2012). Gontijo et al (2012) realizaram um estudo onde foi evidenciado foram dois fatores que afetam a cognição de idosos institucionalizados, independente do sexo, tais como a idade avançada e ao grau de escolaridade.…”
Section: Resultsunclassified
“…A preservação das necessidades do idoso perfaz um caminho que ocasiona a valorização da sua autonomia e eleva a autoestima, apropriando-se de intervenções que previnam o declínio cognitivo e a preservação das habilidades mentais (MELLO; HADDAD; DELLAROZA, 2012). Gontijo et al (2012) realizaram um estudo onde foi evidenciado foram dois fatores que afetam a cognição de idosos institucionalizados, independente do sexo, tais como a idade avançada e ao grau de escolaridade.…”
Section: Resultsunclassified
“…In the present sample, functional status was altered in more than 50% of the participants. The study by Gontijo et al 37 showed that cognitive changes were associated with functional capacity and frailty, regardless of sex. In the study, it was observed that approximately 45% of the participants presented results suggestive of cognitive impairment and 24% presented functional incapacity.…”
Section: Discussionmentioning
confidence: 98%
“…Além disso, o baixo desempenho no MEEM foi frequente. Os estudos de Dantas et al (2013), Gontijo et al (2012), e Mello et al (2012) verificaram que a demência foi a doença que mais causou prejuízos no desempenho funcional dos idosos, devido ao próprio quadro de comprometimento das funções cognitivas provocado pela condição.…”
Section: Caracterização De Funções Psicológicas E Cognitivas Dos Resi...unclassified